Hubungan Motivasi Latihan dan Dukungan Sosial Orang Tua dengan Mental Toughness pada Club Bola Voli Saudara Jaya Grub (SJG) - Muhammad Sarbani; Daryono Daryono; Hengki Kumbara (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This research explores the relationship between training motivation and parental social support on the mental toughness of athletes at the Brother Jaya Group (SJG) Volleyball Club. Mental toughness is considered an important factor that influences athletes' performance and resilience in facing challenges. Using quantitative methods, data was collected through questionnaires that measured training motivation, parental social support, and level of mental toughness. The sample consisted of 50 active young athletes at SJG. Data analysis using the Pearson correlation technique shows that there is a significant positive relationship between exercise motivation and mental toughness, as well as between parental social support and mental toughness. These findings imply that increasing training motivation and social support from parents can increase mental toughness, which has a positive impact on athlete performance. It is hoped that this research will provide insight for coaches and parents in their efforts to support the development of the mental character of young athletes.